Pengalaman Penderita Diabetes Mellitus dalam Pencegahan Ulkus Diabetik - Fitriyanti, Melisa Enni; Febriawati, Henni; Yanti, Lussyefrida (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2019)
Diabetes mellitus (DM) is still a health problem in the world with increasing prevalence. Complications often experienced by people with DM are wounds that do not heal leading to diabetic ulcers. The purpose of this study was to determine the experience of diabetics in preventing diabetes diabetic ulcers in RSUD dr. M. Yunus Bengkulu. This research is a qualitative research with a phenomenological study approach. There were 3 informants who were taken by purposive sampling based on inclusion criteria. Data is taken by in-depth interviews and processed by making a matrix. The results obtained 6 themes, namely aspects of knowledge, aspects of clinical manifestations, aspects of etiology, aspects of risk factors, aspects of prevention, and aspects of family care. Discussion on the aspects of knowledge of the three informants already understand about DM, aspects of clinical manifestations of the 3 informants experiencing the same symptoms, etiological aspects of the causes of DM from information obtained that is due to age, stress and hereditary history, aspects of a large risk factor likely to occur in those who have a hereditary history , The aspect of prevention carried out by the informant is to use medical and non-medical prevention. Aspects of family care 2 informants get family support 1 informant no. In conclusion, the experience of people with diabetes mellitus in preventing diabetic ulcers is herbal medicine, diet, always using footwear to prevent injury. It is hoped that further researchers can develop aspects of preventing diabetes ulcers using quantitative research, and can conduct further research based on aspects of the work.Â Keywords: Â Diabetes mellitus, diabetic ulcers, phenomenological studies Reading